2020
DOI: 10.1186/s12891-020-03413-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between pre-surgical daily opioid use and short-term outcomes following knee or hip arthroplasty: a prospective, exploratory cohort study

Abstract: Background: Retrospective studies have found that daily opioid use pre-arthroplasty predicts worse longer-term service, clinical and patient-reported outcomes. Prospective studies are needed to confirm these observations. This prospective, exploratory study aimed to determine: the proportion of total knee or hip arthroplasty (TKA, THA) patients who use opioids regularly (daily) pre-surgery; if opioid use pre-surgery is associated with acute and subacute outcomes to 12-weeks post-surgery. Methods: Consecutive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
1
13
1
Order By: Relevance
“…22 As opioids are prescribed by internal medicine or primary care providers in 60%-70% of arthroplasty cases, 31 careful coordination and communication between orthopaedic surgeons, patients and other primary care providers as to expectations for opioid use may be paramount to successfully managing prolonged opioid use in this population. 21,31 Opioid use before and after arthroplasty observed in this study were considerably lower than many previous studies, but considerable geographical variation is commonly reported. 19 In the largest series of a US cohort from 2010 to 2014 Jin 19 examined 473 781 subjects and found 31% of TKR and 41% of THR subjects reported opioid use in the month before arthroplasty.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…22 As opioids are prescribed by internal medicine or primary care providers in 60%-70% of arthroplasty cases, 31 careful coordination and communication between orthopaedic surgeons, patients and other primary care providers as to expectations for opioid use may be paramount to successfully managing prolonged opioid use in this population. 21,31 Opioid use before and after arthroplasty observed in this study were considerably lower than many previous studies, but considerable geographical variation is commonly reported. 19 In the largest series of a US cohort from 2010 to 2014 Jin 19 examined 473 781 subjects and found 31% of TKR and 41% of THR subjects reported opioid use in the month before arthroplasty.…”
Section: Discussioncontrasting
confidence: 70%
“…15,16 These rates are more than double the rate of our cohort, and similar to US based studies, but may be influenced by the exclusively veteran sample. Naylor 21 examined 521 THA or TKA subjects in an Australian public hospital cohort of whom 16% reported regular opioid use before, and 30% at 3 months after arthroplasty. In our cohort opioid use within the previous week was reported by 18% before surgery, 28% at 6 weeks and only 7% at 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The connection between preoperative opioid use and chronic postoperative opioid use is well established in orthopaedic literature. 10,[18][19][20][21][22][23][24] This preoperative use is often…”
Section: Risk Factors Preoperative Opioid Usementioning
confidence: 99%